Qualitative comparison of satisfactory stable marriages and marriages with dissatisfaction in infertile couples - Nazemi, Maryam; Amiri Majd, Mojtaba; Ghamari, Mohammad; Asadi, Masoud (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2023)
Background and Aim: The aim of this study was to compare the quality of satisfactory stable marriage and dissatisfaction-associated marriages in infertile couples. Methods: This study was conducted using a qualitative method using the grounded theory method. Using purposeful sampling method, participants were selected according to inclusion criteria and finally 18 infertile couples with satisfactory and stable marriage and 15 infertile couples in marriage with dissatisfaction were interviewed semi-structured and the data were analyzed using Colaizzi's method. Results: The result of open coding was reaching 202 primary codes, 84 sub-categories and 8 main categories and one central category. The central issue in this study is infertility: a dynamic for experiencing genuine and committed love in marriage or its dissatisfaction and disintegration. Data analysis showed that protective and risk factors affecting satisfactory stable marriage and couples with dissatisfaction were defined in three areas of intrapersonal factors, interpersonal and couple factors and factors related to family system. Conclusion: According to the results of this study, achieving acceptance of infertility and the experience of genuine and committed love in marriage or its dissatisfaction and collapse is not accidental in infertile couples, but by choosing constructive and active action or using ineffective strategies created and is an individual, family and interactive process that infertile couples can make with conscious efforts to grow and transcend marriage and take care of it, companionship, couple unity and acquisition. Couple skills and efficient strategies for health and happiness and finally gain satisfaction and stability in marriage and prevent dissatisfaction and breakdown of their marriage.